1976
DOI: 10.1021/bi00654a002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the inactivation of L-lactate oxidase by [the acetylenic suicide substrate]2-hydroxy-3-butynoate

Abstract: 2-Hydroxy-3-butynoate is both a substrate and an irreversible inactivator of the flavoenzyme L-lactate oxidase. The partitioning between catalytic oxidation of 2-hydroxy-3-butynoate and inactivation of the enzyme is determined by the concentration of the second substrate, 0 2 . Rapid reaction studies show the formation of an intermediate which is common to both the oxidation and inactivation pathways. This intermediate appears to be a charge-transfer complex between enzyme-reduced flavin and 2-keto-3-butynoate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…90% for the D-enantiomer. The stereochemistry was confirmed by stereospecific reaction of the pure enantiomers with L-lactate oxidase [14,15] and D-Iactate dehydrogenase [16,17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…90% for the D-enantiomer. The stereochemistry was confirmed by stereospecific reaction of the pure enantiomers with L-lactate oxidase [14,15] and D-Iactate dehydrogenase [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…The mixture had a fluorescence emission with maxima at 525 (identical to that of unmodified FMN) and 420 nm. The latter emission has an excitation spectrum with A max "" 340 nm, which presumably originated from the presence of several decay products of the modified FMN, as in the case of lactate oxidase [14,15]. Thus glycollate oxidase is apparently inactivated by a mechanism 247 similar to that operative with L-lactate oxidase, where a cyclic 4a,5-adduct of the enzyme-bound flavin is formed initially [13,14].…”
Section: Inactivation Of the Enzyme With A-hydroxybutynoic Acidmentioning
confidence: 98%
See 1 more Smart Citation
“…With monoamine oxidase, the substrate analogue propargylamine reacts with the flavocoenzyme to form a covalent N(5) adduct having a cyanine structure (Chuang et al, 1974;Gaertner et al, 1976;Maycock et al, 1976). Several hydroxyacid oxidases [ L-lactate oxidase, Ghisla et al (1976) and Schonbrunn et al (1976); D-and L-lactate dehydrogenases, Walsh et al (1 972); L-hydroxyacid oxidase, Cromartie & Walsh (1975); cytochrome bt, Lederer (1974); glycollate oxidase, Jewess et al ( I 975)J have been reported to be irreversibly inactivated by 2-hydroxy-3-ynoic acids. In the case of L-lactate oxidase, the mechanism of inactivation was found to occur through primary formation of a cyclic N(5)-C(4a) adduct of the inactivator to the flavin coenzyme Schonbrunn et al, 1976) which subsequently decays by hydrolysis of the pyrimidine ring.…”
mentioning
confidence: 99%
“…Since the keto acid derived from the oxidation of this ahydroxy acid is expected to be as reactive as 2-keto-3-butynoate, it is concluded that an allene carbanion produced by abstraction of the a-hydrogen of a H B is the reactive species which covalently adds to the flavin. covalent addition at position N(5) occurred (Maycock et al, 1976), and with the L-specific lactate oxidase, cyclic addition to N(5) and C(4a) of the flavin nucleus was found (Walsh et al, 1972;Ghisla et al, 1976;Schonbrunn et al, 1976). Since these positions of the flavin coenzyme are electrophilic in the oxidized state, an attack of an electrophilic allene is considered unlikely.…”
mentioning
confidence: 99%